2014
DOI: 10.1111/odi.12232
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative hypoalbuminemia as a risk factor for surgical site infection after oral cancer surgery

Abstract: Early postoperative hypoalbuminemia <2.5 g dl(-1) is an independent risk factor for the development of SSI in patients undergoing oral cancer surgery. Clinicians should be aware of the implications of postoperative hypoalbuminemia and consider more intensive postoperative care in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 33 publications
1
32
0
1
Order By: Relevance
“…Although many studies have focused on serum albumin before surgery, Hubner et al [9] showed an early postoperative albumin drop to be related to adverse clinical outcomes. Lee et al [26] found that after oral cancer surgery, patients with postoperative hypoalbuminemia were at risk of surgical site infection. Hypoalbuminemia is thought to be associated with inflammation or previous malnutrition [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have focused on serum albumin before surgery, Hubner et al [9] showed an early postoperative albumin drop to be related to adverse clinical outcomes. Lee et al [26] found that after oral cancer surgery, patients with postoperative hypoalbuminemia were at risk of surgical site infection. Hypoalbuminemia is thought to be associated with inflammation or previous malnutrition [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, low postoperative albumin is affected by many factors. Ge X et al noted that the stress response, perioperative fluid overload, hemodilution, albumin redistribution, a breakdown of metabolism and other comprehensive factors cause postoperative albumin decline [36].Despite this, we still need to be wary of hypoalbuminemia with albumin levels < 3.0 g/dl after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Lee JI et al investigated 337 patients with major oropharyngeal squamous cell carcinoma who underwent clean and contaminated surgery and monitored serum albumin, glucose, and hemoglobin levels during the perioperative period. The results showed that early postoperative hypoalbuminemia <2.5 g/dl was an independent risk factor for SSI in patients who underwent oral cancer surgery [36]. Bohl DD et al also reported that malnutrition increased the risk of periprosthetic joint infection following total joint arthroplasty [37].…”
Section: Discussionmentioning
confidence: 98%